Web-based technologies as key catalysts in improving work productivity and creativity - Blessing Mbatha (Communicare)
The article reports on the usage, benefits and challenges posed by Web-based technologies to civil servants in Zululand District Municipality. Many countries have invested in information and communication technologies (ICTs) as a means of pursuing their organisational goals. This article is informed by the diffusion of innovation theory. Through a survey, key government departments in the Zululand District Municipality were sampled employing systematic and purposive sampling techniques. Questionnaires were administered to 52 civil servants. Fifty responses were received, which translates to an overall response rate of 96%. The findings reveal that while various Webbased technologies are available in all participating government departments in this survey, the numerous challenges identified indicate that utilisation is still a problem. Yet despite these drawbacks, the respondents expressed great eagerness to enhance their ICT skills in order to use Web-based technologies for their own empowerment and also for work productivity. Despite the constraints and challenges encountered in the application and use of Web-based technologies in these government departments, a wide range of Web-based technologies have been adopted to facilitate the exchange of information in the sector.